Media representation of women in Ecuador’s indigenous uprisings: comparative analysis of 1990 and 2019 - Coronado-Otavalo, Ximena; Andrade Ortega, Esthela Alfonsina; Galarza-Ligña , Viviana Noemí; Díaz Gutiérrez, Daniel Alejandro (Historia y Comunicación Social, 2025)
This research analyzes the representation of indigenous women in the uprisings of 1990 and 2019 in Ecuador. Communication and Anthropology are articulated to expose the reduced female presence in the media narrative, dominated by heteropatriarchal and colonial perspectives. The media influence the construction of representations and, by relegating women to secondary roles, they deny their political capacity and reproduce their exclusion. Thirty-two journalistic texts (out of a total of 184) are examined through a CAQDAS analysis. The results show the need to rethink the relationship between gender, media and social movements with an urgent change in news coverage that gives greater visibility to indigenous women as agents of change.